2004
DOI: 10.1128/jb.186.12.4000-4013.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Anti-Sigma Factor SpoIIAB in Regulation of σ G during Bacillus subtilis Sporulation

Abstract: RNA polymerase sigma factor F initiates the prespore-specific program of gene expression during Bacillus subtilis sporulation. F governs transcription of spoIIIG, encoding the late prespore-specific regulator G . However, transcription of spoIIIG is delayed relative to other genes under the control of F , and after synthesis, G is initially kept in an inactive form. Activation of G requires the complete engulfment of the prespore by the mother cell and expression of the spoIIIA and spoIIIJ loci. We screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 51 publications
4
58
0
Order By: Relevance
“…Once translated, G is held inactive by an unknown factor, which was initially thought to be SpoIIAB, with SpoIIAA releasing it from inhibition in a manner analogous to the posttranslational control of F (27,106). However, another study showed that the actions of SpoIIIA were sufficient to release G from the inhibitory action of the unknown factor through a pathway that was facilitated by SpoIIIJ (27,107).…”
Section: E the First Mother Cell-specific Sigma Factor Is Involvedmentioning
confidence: 97%
“…Once translated, G is held inactive by an unknown factor, which was initially thought to be SpoIIAB, with SpoIIAA releasing it from inhibition in a manner analogous to the posttranslational control of F (27,106). However, another study showed that the actions of SpoIIIA were sufficient to release G from the inhibitory action of the unknown factor through a pathway that was facilitated by SpoIIIJ (27,107).…”
Section: E the First Mother Cell-specific Sigma Factor Is Involvedmentioning
confidence: 97%
“…Samples (0?5 ml) of cells in resuspension medium were collected throughout sporulation, and resuspended in the same volume of PBS supplemented with 10 mg ml 21 49,69-diamidino-2-phenylindole (DAPI). Microscope slides were prepared as described previously (Serrano et al, 2004). Images were acquired using a cooled charge couple device (Cooke) on a multi-wavelength wide-field three-dimensional microscopy system (636/1?4 OIL Plan Apochromat objective, Zeiss 100M, Intelligent Imaging Innovation).…”
Section: Methodsmentioning
confidence: 99%
“…Activation also requires completion of engulfment of the prespore by the mother cell (33). SpoIIAB can act as an anti-for G as well as for F (5,15,30) but is now thought not to be a regulator of G activity in the prespore (32).…”
mentioning
confidence: 99%